(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
In this study, a selective electrode was prepared for determination of anion chloride in standard solutions based on a modified carbon paste by mixing 10% silver chloride, 45% graphite and 45% paraffin oil as a plasticizer. The prepared chloride electrode operates at at laboratory temperature, the modified electrode exhibited a linear response and significant Nernstian response with a slope of -55.0 mV/decade in the concentration range from chloride ions significant correlation factor of and response time in the range from (40-35)sec, stability time 20sec, Recovery R% (102.50-99.28) And a relative standard deviation RSD% (8.345-4.179), the analytical detection limit reached and the limit of quantitative detection, , within a confidence interval IS , The proposed method was applied to standard samples and then compared with a reference method, and the accuracy and validity of the used method was confirmed, through the (t) and (f-test) tests, where the value of ’’t’’ was less than the tabular value of t-tab and the value of the F-test was calculated and compared with Ftab at 95% confidence level, it was found that there is no clear difference between the two methods, and that the proposed method is characterized by ease, accuracy and low cost.